Smart City Infrastructure Monitoring using AI and IoT Technologies - Jyoti S. More, Yogesh Jadhav, Vaishali V. Sarbhukan (Bodade) (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Smart cities are developing to effectively manage resources, improve citizen services, and assure sustainable development as civilizations rapidly urbanize. Advanced infrastructure monitoring technologies like AI and IoT are essential for smart city development. This article proposes an AI and IoT-based smart city infrastructure monitoring design. The framework includes IoT sensors on highways, bridges, buildings, water supply systems, and electricity networks throughout the city. These sensors record structure health, traffic movement, ambient conditions, energy usage, and other characteristics in real time. A centralized AI-powered monitoring system analyzes and decides on this data. The monitoring system’s AI algorithms handle massive sensor data using machine learning, deep learning, and predictive analytics. The system can detect structure degradation, transportation congestion, and environmental dangers in real time using pattern recognition and anomaly detection. Predictive analytics lets you schedule maintenance and optimize resource allocation. The monitoring system’s intelligent decision support helps municipal managers make infrastructure management and emergency response choices. Critical occurrences trigger automated warnings and messages to avoid accidents or minimize interruptions. The suggested framework increases municipal infrastructure operating efficiency and public quality of life by assuring safety, dependability, and sustainability. Smart cities can create a more connected, resilient, and sustainable future by using AI and IoT.